Iodine-induced synthetic method and pharmacokinetic study of cis- and trans-crocetin - Li, Boshen; Zhang, Yuxuan; Yang, Zhiqiang; Li, Xiaolin; Yang, Jun; Luo, Kai; Wang, Renjie; Xiao, Chengrong; Li, Maoxing; Gao, Yue (Frontiers in Pharmacology, 2024)
Objective:This experiment aimed to obtain the relatively rare cis-crocetin isomer from natural plants, which predominantly exist in the more stable all-trans configuration. This was achieved through iodine-induced isomerization, followed by purification and structural identification. The study also aimed to compare the pharmacokinetic differences between cis and trans-crocetin in vivo. Methods:Trans-crocetin of high purity was extracted by hydrolysis from gardenia yellow pigment. Cis-crocetin was then synthesized through an optimized electrophilic addition reaction induced by elemental iodine, and subsequently separated and purified via silica gel column chromatography. Structural identification of cis-crocetin was determined using IR, UV, and NMR techniques. In vivo pharmacokinetic studies were conducted for both cis and trans-crocetin.In addition to this, we have conducted a comparative study on the in vivo anti-hypoxic activity of trans and cis-crocetin. Results:Under the selected reaction conditions using DMF as the solvent, with a concentration of 2.5 mg/mL for both trans-crocetin and iodine solution, and adjusting the illumination time according to the amount of trans-crocetin, the rate of iodine-induced isomerization was fastest. Cis-crocetin was successfully obtained and, after purification, its structure was identified and found to be consistent with reported data. Cis-crocetin exhibited a faster absorption rate and higher bioavailability, and despite its shorter half-life, it could partially convert to trans-crocetin in the body, thereby extending the duration of the drug's action within the body to some extent. Conclusion: This study accomplished the successful preparation and structural identification of cis-crocetin. Additionally, through pharmacokinetic studies, it uncovered notable variations in bioavailability between cis and trans-crocetin. These findings serve as a solid scientific foundation for future functional research and practical applications in this field.